Water Quality Status of the SDGs Lake of IPB Campus, Dramaga, Bogor, West Java: Status Mutu Kualitas Air Danau SDGs-Kampus IPB Dramaga, Bogor, Jawa Barat - Admiral Farouk Sabzevar, Andi; Zainalarifin, Jauhar; Lolon, Meitin; Sari Andhika, Laila; Annisa Rusli, Andi; Khasanah, Siti (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, IPB University, 2025)
Lakes are aquatic ecosystems surrounded by land. Lakes have many uses, namely as habitats for aquatic biota and for tourism, mitigation, and education. Human activities around Lake SDGs IPB Dramaga have a negative impact on the lake environment. This study aims to compare the water quality status of SDGs lakes with CCME and the Pollution Index. The research used two time periods, namely October 2024 and March 2024, with three station points. The research results show that four parameters do not meet quality standards, with more parameters occurring in October 2023. Water quality status measurement using the lake pollution index is in the moderate category, while for CCME WQI, the lake is classified as in poor condition. The pollution index has a smaller standard error and deviation than the CCME WQI method. Hence, the pollution index method is more accurate in measuring the water quality status in Lake SDGs IPB Dramaga in these two periods.